Visiting friends and relatives (VFR) market: a conceptual framework - Ramachandran, Sridar (Tourism Educators Association of Malaysia, 2006)
This paper examines a specific market segment – the visiting friends and relatives (VFR) market – within a broader context of the tourism market. Misconception of VFR as a non-lucrative market segment and the fact that VFR appeared as one of the least researched areas has been the underpinning reasons to embark on this study. This paper is dedicated to understand the meaning of visiting friends and relatives. An extensive literature review revealed five emergent themes within the context of the VFR research, which includes: motivation, conceptualisation, distance, sector, and measurement. Realising VFR’s contribution to the broader tourism market, this paper reveal the significance of the VFR market within the broader tourism market segments in order for both academics and practitioners to have renewed appreciation toward this subject matter.